Perceptions of men towards contraceptive use by their spouses. - Сhipeta, Мetty С. (Kamuzu University of Health Sciences, 2022)
This is a descriptive study carried out in order to explore the perceptions of men on contraceptive use by their spouses. The study specifically sought to explore the role of men in family planning, to determine the extent to which men accept contraceptive use by their spouses, to determine benefits of contraceptive use, the barriers to contraceptive use amongst married men and their spouses, and to determine sources of information on contraceptives. Results have shown that men accept contraceptive use by their spouses on condition that they themselves should make that decision. However, they support their spouses on contraceptive use. Data has further shown that very few men indulge themselves in practical roles. The findings further reveal that several variables affect the perceptions of men towards contraceptive use by their spouses. These are as follows: Educational level of the couple, age, culture, religion, economic constraints and frequency of pregnancies.